Efficacy of Hyperosmolar Dextrose Injection for Osgood–Schlatter Disease: A Systematic Review with Meta-Analysis - Hye Chang Rhim; Lori B. Bjork; Jaehyung Shin; Jewel Park; Stephanie E. DeLuca; Katelyn C. McCarron; Ki-Mo Jang; Chris Ha (Diagnostics)
Background/Objectives: Although Osgood–Schlatter disease (OSD) is often self-limiting following apophyseal closure, it may cause persistent symptoms into adulthood, affecting physical and functional activities. The purpose of this systematic review is to summarize the current evidence on the efficacy of hyperosmolar dextrose injection for patients with OSD unresponsive to conservative treatment. Methods: Multiple databases were searched for studies investigating the efficacy of hyperosmolar dextrose injection in patients with OSD. Two reviewers independently extracted data and evaluated the risk of bias. Meta-analyses were performed to compare hyperosmolar dextrose injection with placebo injections. Results: Four studies including three randomized controlled trials (RCTs) and one case series involving a total of 166 (162 males and 4 females) patients with 184 knees were included in this review. At three months, there was no significant difference in patient-reported improvement from baseline between hyperosmolar dextrose injection and placebo injections (standardized mean difference [SMD] = 1.92, 95% confidence interval [CI], −0.12 to 3.96; I2 = 96.2%). However, a meta-analysis of two RCTs including athletic pediatric patients found a pooled risk ratio of 2.11 (95% CI: 1.12 to 3.98, I2 = 30.73%) for pain-free return to sports at three months. In addition, at one year, a meta-analysis of two RCTs showed greater patient-reported improvement from baseline with hyperosmolar dextrose injection compared to placebo (SMD = 1.09, 95% CI, 0.62 to 1.56; I2= 0%). Conclusions: Based on the limited number of RCTs, although no improvement in patient-reported outcomes is seen at three months, hyperosmolar dextrose injection may safely facilitate a pain-free return to sports at three months and lead to patient-reported improvement at one year. However, further high-quality RCTs are needed to substantiate these findings.